A CO 2 -Free Synthetic Host–Odor Mixture That Attracts and Captures Triatomines: Effect of Emitted Odorant Ratios - Guidobaldi, Fabio (2016)
Triatomines, vectors of Chagas Disease, are hematophagous insects. Efforts have been made to develop synthetic attractants based on vertebrate odor—to lure them into traps. However, because those lures are not practical or have low capture efficiency, they are not in use in control programs. Therefore, more work is needed to reach a practical and efficient odor lure. Recently, a three-component, CO 2 -free, synthetic blend of vertebrate odor (consisting of ammonia, L -(+)-lactic acid, and hexanoic acid), known as Sweetscent (Biogents AG, Regensburg, Germany), was shown to attract and capture triatomines in the laboratory. In this study, using a trap olfactometer and an odor blend with constituents similar to those of Sweetscent (delivered from low-density polyethylene sachets) we found that the odorant ratios of the mixtures have a strong effect in the capture of triatomines. The blend with the most efficient combination of odorant ratios evoked ca. 81% capture in two relevant triatomine species. In the case of the most effective odor mixtures, we measured the odor mass emission for the three components of the mixture and therefore were able to estimate the odorant ratios emitted that were responsible for such a high capture performance. Thus, in those mixtures, pentanoic acid was the main component (ca. 65 %) followed by ammonia (ca. 28%) and, L (+)-lactic acid (ca. 7 %). Our results are encouraging as efficient, practical, and cheap odor baits to trap triatomines in the field would be within reach. The odor-delivery system used should be improved to increase stability of odor emission.